Estimates of heritability and phenotypic correlations for size and weight of Yorkshire litters - Fávero, Jerônimo Antonio (Pesquisa Agropecuaria Brasileira, 2014)
The genetic and phenotypic parameters of nine litter traits from a group of Yorkshire first litter gilts were evaluated for the purpose of determining the effect of litter size of the mother on the first litter of the daughters. Linear regression coefficients of consanguinity determined for each trait studied, although insignificant (P>0,05) confirm results of earlier studies showing the mating of closely related animals to be a negative factor on litter size and weight. An analysis of phenotypic correlations between litter traits supported the conclusion that the number of liveborn piglets and the number of 21 -day old suckling pigs could be arranged by index to define maternal ability. Finally, the existence of negative maternal atmosphere during the suckling period, presenting a reproductive disadvantage at first parturition in females raised in largo litters, is suggested. Standardization of litter size of up to eleven suckling piglets is also recommended during the nursing period as a means of diminishing the negative effects described above.